Association of gastric cancer risk factors with DNA methylation levels in gastric mucosa of healthy Japanese: a cross-sectional study. (8th September 2015) - Shimazu, Taichi; Asada, Kiyoshi; Charvat, Hadrien; Kusano, Chika; Otake, Yosuke; Kakugawa, Yasuo; Watanabe, Hidenobu; Gotoda, Takuji; Ushijima, Toshikazu; Tsugane, Shoichiro
Summary: Smoking habits and green/yellow vegetable intake were associated with DNA methylation levels in gastric mucosae of healthy individuals with current Helicobacter pylori infection. These risk factors may modify the effect of H.pylori on methylation in gastric mucosa. Abstract : Helicobacter pylori infection induces aberrant DNA methylation, and methylation levels of several specific marker genes in gastric mucosa are associated with gastric cancer risk. However, it is unclear whether gastric cancer risk factors are associated with methylation levels of marker genes in healthy individuals. We conducted a cross-sectional study of 281 Japanese cancer screenees aged 40–69 years with no history of H.pylori eradication therapy who responded to a validated food frequency questionnaire. DNA methylation levels of marker genes ( miR-124a-3, EMX1 and NKX6-1 ) in gastric mucosa were quantified by real-time methylation-specific polymerase chain reaction. A multivariate beta regression model was used to investigate the association of pack-years of smoking and intakes of green/yellow vegetables, fruit and salt with methylation levels of marker genes. All analyses were stratified by H.pylori status. We found 2.5 to 34.1 times higher mean methylation levels among those with current H.pylori infection ( n = 117) compared to those without ( n = 164). After adjustment for potential confounders, we found increased levels of miR-124a-3 methylation according to pack-years of smoking and decreased levels of methylation according to green/yellow vegetable intake. We did not detect these associations among those without H.pylori infection. In conclusion, smoking habits and green/yellow vegetable intake were associated with DNA methylation levels in gastric mucosae of healthy individuals with current H.pylori infection. Our study suggests that these risk factors may modify the effect of H.pylori on methylation induction and maintenance in gastric mucosa.